Penerapan Sak EMKM dalam Penyusunan Laporan Keuangan pada Koperasi Simpan Pinjam Kasih Ibu - Mentari Podungge, Sri; Bokiu, Zulkifli; Pakaya, Lukman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine how the implementation of SAK EMKM and the obstacles in preparing financial reports at the Kasih Ibu Savings and Loans Cooperative. This study uses a descriptive quantitative method with data collection using observation, interview and documentation methods. The informants in this study were the administrators and employees of the Kasih Ibu Cooperative and SMEs. The results of this study indicate that the Kasih Ibu Savings and Loans Cooperative has not fully implemented SAK EMKM. This is because the Kasih Ibu Savings and Loans Cooperative has not made notes on the financial statements in its financial statements, which is one of the indicators that is the basis for seeing whether an entity has implemented SAK EMKM or not in preparing their financial statements, but the Kasih Ibu Cooperative has prepared a profit and loss report and financial position report. Then related to the obstacles in the implementation of SAK EMKM at the Kasih Ibu Cooperative, it was found that there was still a lack of knowledge and understanding regarding the preparation of notes to financial statements (CALK) which was one of the obstacles in the implementation of SAK EMKM. In addition, the absence of policies or regulations that require the implementation of SAK EMKM also contributed to the inhibiting factor.